Literasi Kurasi Digital Bagi Guru Pendidikan Agama Islam - Moh Hamdani; Novita Sari; Evi Fatimatur Rusydiyah (UMSU, 2022)
This study aims to describe the implementation of digital curation literacy for PAI teachers in elementary schools throughout the city of Surabaya. The population in this study were all PAI teachers who taught in all elementary schools in the city of Surabaya, totaling 46 teachers. Samples were taken using a proportional random sampling technique, but the samples taken were teachers who had implemented digital curation literacy. The final sample is 26 teachers. In this study a questionnaire was used to collect data which included indicators of the implementation of digital curation literacy as a whole which were spread over 6 statement items, using a Likert scale with a score of 1 to 5. The results showed that in general PAI teachers in elementary schools in Surabaya City for the academic year 2021/2022 those who have implemented digital curatorial literacy obtained an average score of 88.8% in the five sub-variables of implementing digital curatorial literacy, with the category mostly implemented.